2020
DOI: 10.1186/s12865-020-00348-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Interleukin-35 suppresses peripheral CD14+ monocytes function in patients with Kawasaki disease

Abstract: Background: Interleukin-35 (IL-35) is a newly identified IL-12 cytokine family member, which regulates the activity of immune cells in infectious diseases and autoimmune disorders. However, the regulatory function of IL-35 in Kawasaki disease is not well elucidated. Methods: Thirty-three patients with Kawasaki disease and seventeen healthy controls were studied. Peripheral IL-35 concentration was measured by enzyme linked immunosorbent assay. CD14 + monocytes were purified, and mRNA expression of IL-35 recepto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Subsequently, Wang et al identified that numbers of i35-Bregs were remarkably increased with the accumulation of CD14 + monocytes (37). Moreover, IL-35 suppressed CD14 + monocytes induced naive CD4 + T cell activation and the production of TNF-a and granzyme B, inhibiting cytotoxicity of them, whereas this effect has not been reported in TME (87). Further studies are needed to elucidate that function of IL-35 in the complex role of endothelial cells and monocytes during the angiogenesis in the TME.…”
Section: Interactions Between Il-35 and Macrophages In The Tmementioning
confidence: 99%
“…Subsequently, Wang et al identified that numbers of i35-Bregs were remarkably increased with the accumulation of CD14 + monocytes (37). Moreover, IL-35 suppressed CD14 + monocytes induced naive CD4 + T cell activation and the production of TNF-a and granzyme B, inhibiting cytotoxicity of them, whereas this effect has not been reported in TME (87). Further studies are needed to elucidate that function of IL-35 in the complex role of endothelial cells and monocytes during the angiogenesis in the TME.…”
Section: Interactions Between Il-35 and Macrophages In The Tmementioning
confidence: 99%
“…Evidences showed that IL-35 expression was obviously elevated in HCV patients, and had a positive association with DNA and RNA load of virus ( Liu et al, 2017 ). Langhans et al have found that the viral core antigen could induce the production of specific Tregs in chronic viral infection patients ( Xing and Tian, 2020 ). Treg cells comprised 5% to 10% of CD4+ T cells.…”
Section: The Regulatory Role Of Interleukin-35 In Liver Diseasesmentioning
confidence: 99%
“…Furthermore, circulating IL-35 expression level might suggest the dysfunctional immune system in anti-tumor response, showing the activation of Tregs and the apoptosis of CD8+ T cell ( Heim et al, 2019 ). Moreover, IL-35 expression level was positively correlated with intrahepatic cholangiocarcinoma (ICC) aggressiveness, and served as an independent prognostic factor ( Xing and Tian, 2020 ). IL-35R was composed by heterodimer of IL-12Rβ2 chain and gp130 chain or homodimers of each chain.…”
Section: The Therapeutic Potential Role Of Interleukin-35mentioning
confidence: 99%
See 2 more Smart Citations